2010
DOI: 10.1007/s12195-010-0136-9
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Membrane Sensitivity to Shear Stress is Lipid Domain Dependent

Abstract: Blood flow-associated shear stress causes physiological and pathophysiological biochemical processes in endothelial cells that may be initiated by alterations in plasma membrane lipid domains characterized as liquid-ordered (lo), such as rafts or caveolae, or liquid-disordered (ld). To test for domain–dependent shear sensitivity, we used time-correlated single photon counting instrumentation to assess the photophysics and dynamics of the domain-selective lipid analogues DiI-C12 and DiI-C18 in endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 74 publications
4
42
0
Order By: Relevance
“…GPCRs, such as rhodopsin have also been shown to be very sensitive to comparable changes in membrane thickness and lipid composition (which affects various bilayer parameters, including fluidity) [9,94,95]. Notably it has also been reported that mechanical perturbation of the cell membrane leads to membrane fluidity changes of similar magnitude as determined in this study [22,23,96,97]. Although changes in membrane fluidity may not directly affect conformational equilibrium between active and inactive states of the membrane protein since populations of conformational states are primarily determined by the free energy differences, the fluidity could have an effect on downstream signaling.…”
Section: Discussionsupporting
confidence: 68%
“…GPCRs, such as rhodopsin have also been shown to be very sensitive to comparable changes in membrane thickness and lipid composition (which affects various bilayer parameters, including fluidity) [9,94,95]. Notably it has also been reported that mechanical perturbation of the cell membrane leads to membrane fluidity changes of similar magnitude as determined in this study [22,23,96,97]. Although changes in membrane fluidity may not directly affect conformational equilibrium between active and inactive states of the membrane protein since populations of conformational states are primarily determined by the free energy differences, the fluidity could have an effect on downstream signaling.…”
Section: Discussionsupporting
confidence: 68%
“…tension) of the membrane. [23][24] In time-resolved fluorescence measurements, we observe a clear difference in the fluorescence lifetime of the DiI between the living cell and the GPMV. Suggesting the cell membrane may be maintained in a different region of the phase diagram and may even actively avoid a temperature-driven miscibility phase transition.…”
Section: Introductionmentioning
confidence: 89%
“…8 The fluorescence lifetime of DiI is linearly correlated with the local viscosity of the dye's surrounding environment, so DiI fluorescence lifetime can be used as membrane tension reporter. 23 We collected data without distinguishing the different phases of phase separated GPMV to correctly mimic the data collection from the cell membrane with hypothetical nano-scale phase separation. …”
Section: Lifetime Measurementmentioning
confidence: 99%
“…Recent MD simulation results suggested that the fluorescence lifetime of DiI chromophores embedded in lipid bilayer is an effective indicator of relative membrane tension, 119 which was confirmed in experiments. 120 Indeed, fluorescence lifetime measurements of DiI-C 12 within cells demonstrated that cell membrane is less tense on softer PA gels. 117 This predicts that the cellular uptake of cells on softer PA gels or denser fibrous substrates is higher on a per membrane area basis.…”
Section: Local Mechanical Environmental Effectsmentioning
confidence: 99%